17.6% stabilized efficiency in low-temperature processed planar perovskite solar cells1. Issue 8 (29th August 2015) - Tao, Chen; Neutzner, Stefanie; Colella, Letizia; Marras, Sergio; Srimath Kandada, Ajay Ram; Gandini, Marina; Bastiani, Michele De; Pace, Giuseppina; Manna, Liberato; Caironi, Mario; Bertarelli, Chiara; Petrozza, Annamaria
<x xml:space="preserve">Abstract</x> Compact TiO2 is replaced by a low-temperature solution-processed TiOX/60-PCBM layer for electron extraction in perovskite solar cells with high steady conversion efficiencies.